Mukena: A balance between the Indonesian women's prayer dress and the hadiths on the prayer of prophet's wives | موكينا: موازنة بين لباس صلاة المرأة الإندونيسية وأحاديث صفة صلاة أمهات المؤمنين - Fatihunnada Fatihunnada; Nur Faricha; Hasan Basri Salim (Al-Zahra: Journal for Islamic and Arabic Studies)
Mukena is a women's prayer dress in Indonesia. It is well known that the Nine Saints knew her in the fourteenth century AD, but the truth is that Nyai Mukena first knew her in Cirebon. Mokina is considered an Indonesian women's prayer dress. The prayer dress has standards that must be met for the validity of its use in prayer. The mothers of the believers wore the dress of prayer for the Arabs in the past, as mentioned in some narrations. This research analyzes Mukena's hadiths about the dress of the mothers of the believers' prayer.